2022
DOI: 10.3389/fbioe.2022.966866
|View full text |Cite
|
Sign up to set email alerts
|

The roles and applications of neural stem cells in spinal cord injury repair

Abstract: Spinal cord injury (SCI), which has no current cure, places a severe burden on patients. Stem cell-based therapies are considered promising in attempts to repair injured spinal cords; such options include neural stem cells (NSCs). NSCs are multipotent stem cells that differentiate into neuronal and neuroglial lineages. This feature makes NSCs suitable candidates for regenerating injured spinal cords. Many studies have revealed the therapeutic potential of NSCs. In this review, we discuss from an integrated vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…Various cell types have been studied as sources of cell replacement therapy for SCI treatment. Although some issues must be overcome, the use of neuronal stem cells/neuronal precursor cells (NSCs/NPCs), derived from embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), is promising [ 4 , 5 ]. Several studies using animal models of SCI have demonstrated that locomotion is recovered, after SCI, by the transplantation of NSCs/NPCs derived from ESCs and iPSCs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various cell types have been studied as sources of cell replacement therapy for SCI treatment. Although some issues must be overcome, the use of neuronal stem cells/neuronal precursor cells (NSCs/NPCs), derived from embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), is promising [ 4 , 5 ]. Several studies using animal models of SCI have demonstrated that locomotion is recovered, after SCI, by the transplantation of NSCs/NPCs derived from ESCs and iPSCs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…NSCs play important roles in nervous system development and neurogenesis. NSCs can differentiate into neurons and neurogliocytes, maintaining the capability of disintegration, multiplication, and maturity in nerve injury and neurodegenerative disorders 17 . However, NSCs still lack the ability to promote proliferation, migration, and differentiation in adults 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, neurogenesis is the main obstacle to successful SCI repair. [ 18 ] Modifications should be made to endow MEX with the neural regenerative ability. Laminin is an extracellular matrix protein consisting of α , β , and γ polypeptide chains which regulates many cellular functions of neuronal cells.…”
Section: Introductionmentioning
confidence: 99%